Professionalism Of Islamic Religious Education Teachers - Ibnudin; Akhmad Syatori (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
Professional educators are educators who have the ability to carry out educational and teaching tasks. In other words, a professional educator is someone who has special abilities and expertise in the field of education. The teacher is a key focus in achieving educational goals. This means that the teacher is a profession that demands expertise, responsibility and loyalty. Professionalism is an understanding that teaches that every job must be done by a professional person. Work according to Islam must be done because of Allah. So Profession in Islam must be lived because you feel that it is God's command. In reality the work is done for other people, but the underlying intention is Allah's commandment. In Islam every job must be done professionally, in the sense that it is done optimally, honestly, disciplined and diligently. Therefore, teachers of Islamic religious education in schools or madrasas must be creative, innovative and consistently uphold Islamic values and professional values through a directed institutional development program. Every school or madrasa must be able to develop professional attitudes both internally and externally. Going in means being an expert in the field of education and teaching Islamic Religious Education, while going out means being able to seize opportunities and become a useful figure of Islamic religious education teacher in society so that financially and socially it will be stronger. Education in Islam is not only intended to give birth to good human beings who are intellectually intelligent, but also good human beings from the perspective of the creator, namely having faith and piety to Him. Therefore, being a professional teacher is an obligation for a Muslim and is a religious order.